Program Literasi Komunikasi Gastronomi untuk City Branding Berkelanjutan: Studi di Pecinan Glodok - Rosmawaty Hilderiah Pandjaitan; Santa Lorita; Dewi Murtiningsih (Jurnal Pustaka Dianmas, 2026)
Glodok Chinatown in West Jakarta possesses a rich Chinese–Betawi gastronomic heritage with significant potential to strengthen Jakarta's city branding. However, this potential has not been fully utilized due to limited gastronomic communication literacy, inadequate culinary storytelling, and insufficient community participation in cultural tourism development. This Community Service Program (CSP) aimed to enhance community gastronomic communication literacy through a Community-Based Tourism (CBT) approach. The program was implemented in four stages, comprising needs assessment, knowledge transfer, storytelling workshops and practical sessions, and sustainability mentoring, involving 45 participants representing micro, small, and medium enterprises (MSMEs), professional associations, local government, tourism awareness groups (Pokdarwis), Family Welfare Movement (PKK) members, and youth communities. Program evaluation employed a simple post-test design, participatory observation, and participant feedback covering the dimensions of knowledge, attitudes, and behavioural intentions. The findings indicate that 100% of participants recognized Chinese–Betawi cuisine as part of Jakarta's cultural heritage, 100% expressed willingness to support the preservation and promotion of local gastronomy, and 100% intended to disseminate information about Glodok's culinary heritage through interpersonal communication and social media. Furthermore, all participants rated the program's usefulness 10 out of 10. Beyond improving community literacy, the program produced practical outputs in the form of gastronomic storytelling materials and a community-based gastronomic communication literacy model that contributes to strengthening Jakarta's sustainable city branding through multi-stakeholder collaboration, digital media utilization, and community empowerment.